Analisis Implementasi Gerakan Literasi di Kelurahan Uluindano - Della Rumampuk; Winda Lidia Lumbantobing (Mathematics Education Study Program, 2025)
Literacy development is a strategic effort to improve the quality of human resources toward a more independent and competitive society. This study aims to analyze the implementation of the Literacy Movement in Uluindano Village as a form of community-based literacy empowerment. The research employs a descriptive qualitative approach with data collected through observation, interviews, and documentation. Data analysis follows the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing, while data validity is ensured through source and technique triangulation. The findings indicate that the implementation of the literacy program takes place through the use of reading spaces and shared reading activities, which are mostly attended by children. Literacy development in the village is reflected in the increasing reading interest among children; however, adult participation remains limited. Major challenges include inadequate facilities, low digital literacy, the absence of local literacy policies at the village level, and the lack of reading materials relevant to adult age groups. This study concludes that strengthening literacy in Uluindano Village requires the establishment of local policy frameworks, improved literacy facilities, the provision of additional reading materials, and broader community involvement to ensure the sustainability of literacy programs.